Symbolic Universes in Time of (Post)Crisis The Future of European Societies - Salvatore, Sergio; Fini, Viviana; Mannarini, Terri; Valsiner, Jaan.; Veltri, Giuseppe Alessandro; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book investigates whether, how and where the cultural milieu of European societies has changed as a result of the socio-economics crisis. To do so, it adopts a psycho-cultural approach, which views the cultural milieu as a set of meanings, placing the generalized image social actors have of themselves, the world, events and their relationships in the context of the socio-political and institutional environment, including policies. By analyzing the changes in cultural milieu and social identity, the book develops strategic and methodological guidelines for the design of post-crisis policies, providing a concept of how the cultural dynamics are associated with certain individual characteristics and specific socio-economic phenomena.
Liquid crisis: narratives, concepts, imaginaries, politics -- The theoretical and methodological framework. The Semiotic Cultural Psychology and the notion of symbolic universe -- The map of symbolic universes -- European territories and symbolic universes -- Symbolic universes, economic and institutional scenarios, models of actions -- Cultural rupture and subjectivity: Shifts in the personal and professional identity of mental health professionals in times of crisis -- Teacher Evaluation Policies in Times of Crisis and Symbolic Universes: An Exploratory Analysis of the Greek Educational Context Symbolic universes and discursive enactment -- The representation of health and wellbeing in UK -- Symbolic universes and (post)crisis scenarios -- Perspective of development and new models of policies.
Keywords: Sociology -- Methodology; Social psychology; Political planning; Sociological Methods; Social Psychology; Public Policy